Agglomeration of Economic Activities of Fisherman Communities In Jenilu Village Belu District - Muhammad Husain Hasan; Sukmawati Sukmawati; Sunimbar Sunimbar (JAMBURA GEO EDUCATION JOURNAL, 2023)
Research on the phenomenon of agglomeration of community economic activities needs to be carried out to see its impact on regional development, especially in border areas. Grouped economic activities can be a consideration for the government in taking economic policies in order to improve people's welfare. This study aimed to find out: 1) where and how the economic activities of the fishing community in Jenilu Village experience concentration or agglomeration; 2) what are the characteristics of the economic activities of the fishing community in Jenilu Village; and 3) what government policies should be taken to accelerate development in Jenilu Village. This type of research is a qualitative field exploration with data collection techniques of observation, interviews, and documentation studies. The research results show: 1) the economic activities of the fishing community in Jenilu Village experience agglomeration or grouping in the Atapupu area due to the historical value of this area which has long been the center of community activities and also the existence of infrastructure support including good access to cross-country roads, markets, and ports; 2) 80% of the people of Jenilu Village work as fishermen with a low-income level of an average of Rp. 1000,000,- per month, still relying on simple fishing equipment such as fishing rods, nets, and motorized boats, and the main types of a catch include tuna, tuna, yellow stripe, and mackerel; 3) the regional government is expected to be able to improve the quality of human resources and build infrastructure in this region to support the development of the main border gate area which has not been maximized.